2015
DOI: 10.3892/mco.2015.557
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio is an independent prognostic factor in patients with recurrent or metastatic head and neck squamous cell cancer

Abstract: Abstract. The neutrophil to lymphocyte ratio (NLR) has been widely investigated for its prognostic significance in cancer.In the present study, we aimed to determine whether NLR is a prognostic factor in patients with recurrent or metastatic head and neck squamous cell cancer (HNSCC). A total of 79 patients from the Akdeniz University database were retrospectively analyzed. The cut-off NLR was set at 2.93; patients with NLR >2.93 had a median overall survival (OS) of 12.1 months, whereas the median OS was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Finally, 25 studies with 28 cohorts fulfilled the criteria and were eligible in this meta‐analysis. All of them are retrospective observation studies.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 25 studies with 28 cohorts fulfilled the criteria and were eligible in this meta‐analysis. All of them are retrospective observation studies.…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow chart of the systematic review can be found in Figure . An initial search done using the search strategy (Supporting Materials) obtained an initial 900 results.…”
Section: Methodsmentioning
confidence: 99%
“…The NLR is a well-known marker of inflammation. Recent studies stressed that an elevated NLR increased the risk of recurrence and distant metastasis and that it was therefore associated with a poor prognosis in head, neck, and thyroid cancers (Lang et al, 2014;Haddad et al, 2015;Salim et al, 2015). A previous study suggested that an increased NLR indicated an increased risk of metastasis in NPC (Jin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%